2014
DOI: 10.1098/rspb.2014.1061
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal distance is influenced by parental and grand-parental density

Abstract: Non-genetic transmission of information across generations, so-called parental effects, can have significant impacts on offspring morphology, physiology, behaviour and life-history traits. In previous experimental work using the two-spotted spider mite Tetranychus urticae Koch, we demonstrated that dispersal distances increase with local density and levels of genetic relatedness. We here show that manipulation of parental and grand-parental density has a significant effect on offspring dispersal distance, of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 61 publications
0
54
0
Order By: Relevance
“…In recent studies, we have shown the variation in density during the non-breeding season influences the dry weight of flies surviving to enter the breeding period (Betini et al 2013b), which then carries over to influence reproductive output (Betini et al 2013a). However, in other populations, the decision to disperse could also be influenced by past densities acting through other mechanisms (Morris and Diffendorfer 2004), such as maternal effects (Bitume et al 2014), access to mates (Stamps 1991), aggressive interactions (Hestbeck 1982), mating status (Simon et al 2011), foraging behavior (Edelsparre et al 2014), or competitive environment (Innocent et al 2010). For example, individuals may be more willing to disperse in a given season if their assessment of the competitive environment is Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, we have shown the variation in density during the non-breeding season influences the dry weight of flies surviving to enter the breeding period (Betini et al 2013b), which then carries over to influence reproductive output (Betini et al 2013a). However, in other populations, the decision to disperse could also be influenced by past densities acting through other mechanisms (Morris and Diffendorfer 2004), such as maternal effects (Bitume et al 2014), access to mates (Stamps 1991), aggressive interactions (Hestbeck 1982), mating status (Simon et al 2011), foraging behavior (Edelsparre et al 2014), or competitive environment (Innocent et al 2010). For example, individuals may be more willing to disperse in a given season if their assessment of the competitive environment is Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Given that dispersal can be energetically costly (Bonte et al 2011), delayed effects of density on dispersal caused by temporal variation in resources could be a widespread, but underappreciated, phenomenon (Morris and Diffendorfer 2004, Debeffe et al 2012, Bitume et al 2014. This is particularly important because humans are creating an increasingly disturbed and fragmented landscape, and it is widely recognized that the persistence of a species relies on the ability to explore and move through the landscape (Parmesan 2006, Swift and Hannon 2010, Post 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent genetic dispersal syndromes at the individual‐level are neither expected to maximise fitness. Like life‐history traits related to reproduction and aging (Lindström 1999), dispersal is now acknowledged to be context‐ and density‐dependent (Clobert et al , De Meester and Bonte , Bitume et al , ) and thus highly heterogeneous when studied at the phenotypic level. An analysis of phenotypic data on dispersal and movement of European butterflies revealed at least as much variation within as among species (Stevens et al ).…”
Section: Is Dispersal Genetically Integrated In Life Histories?mentioning
confidence: 99%
“…Within a food web perspective, phenotypic variation has been demonstrated to affect interaction strengths between prey and predators (terHorst et al ). Carry‐over effects across life stages (Van Allen and Bhavsar ) or even generations (Bitume et al , ) can be particularly relevant to maintain and generate spatiotemporal variation in demography among local populations (Benard and McCauley ).…”
Section: Consequences – Condition Dependencymentioning
confidence: 99%
“…Our results are consistent with the observation that the dispersal distance of offspring is strongly affected by maternal and grand-maternal environments (Bitume et al. 2014). We could thus infer that females reared on the tomato common environment produced adults with a dispersal capacity higher than those from females reared on the cucumber common environment, this capacity potentially being adaptive for searching for a more suitable host.…”
Section: Discussionmentioning
confidence: 99%